Comparison of the efficiencies of intrathecal and intraganglionic injections in mouse dorsal root ganglion - Aydın, Mehmet Şerif; Yiğit, Esra Nur (Turkiye Klinikleri, 2023)
Background/aim: Dorsal root ganglia (DRG) are structures containing primary sensory neurons. Intraganglionic (IG) and intrathecal (IT) applications are the most common methods used for viral vector transfer to DRG. We aim to compare the efficiencies and pathological effects of IT and IG viral vector delivery methods to DRG, through in vivo imaging. Materials and methods: Mice were divided into four groups of six each: IT, IG, IT-vehicle, and IG-vehicle. Adeno-associated virus (AAV) injection was performed for EGFP expression in IT/IG groups. DRGs were made visible through vertebral window surgery and visualized with multiphoton microscopy. After imaging, spinal cords and DRGs were removed and cleared, then imaged with light sheet microscopy. Results: No neuronal death was observed after IT injection, while the death rate was 17% 24 h after IG injection. EGFP expression efficiencies were 90%–95% of neurons in both groups. EGFP expression was only observed in targeted L2 DRG after IG injection, while it was observed in DRGs located between L1-L5 levels after IT injection. Conclusion: IT injection is a more suitable method for labeling DRG neurons in neurodegenerative injury models. However, when the innervation of DRG needs to be specifically studied, IT injection reduces this specificity due to its spread. In these studies, IG injection is the most suitable method for labeling single DRG neurons.
Keywords: Dorsal Root Ganglion; Intraganglionic Injection; Intrathecal Injection; Multiphoton Microscopy